Problems of Texts In Quran and Torah: Suspicions of Quotation and the Originality of the Provisions - Hameed Al-Baiati, Ra’ad; Saleem Sadiq, Shihab (Opción, 2019)
The present paper concerns the religious beliefs and spiritual concepts. The paper attempts to be neutral and stands away from the religious and mythol- ogy sides. This is to achieve the scientific and objective approach and to be neutral between the Qur’an and Torah as heavenly texts. It is worthy to say that over a long time, both of them have been subjects to be analyzed and criticized. The researchers should be neutral in tackling and analyzing the Biblical and the Qur’anic text, and to determine the suitability of each one in dealing with the contemporary event in terms of religious judgment according to the principles of interpretation and its significance to the addressees. The problem of the study may be summarized in the following questions: 1. Does the quotation in the religious text from human heritage (literary and ideologi- cal) have negative reflections on the originality of the idea? 2. Do the Qur’anic and Biblical verse include literature issue or it is merely affecting with the old mythology? 3. What are the factors that lead to those quotations? And have the time and the place any effect in those quotations? The paper aims at: a. Identifying the motives that lead the contemporary thought to consider the holy texts and to find out whether this consideration is to gain special benefits or it may cause perditions .b. Specifying the hermeneutique arise from the Western renaissance projects. This curriculum which came from the Western culture has been attached the religion texts spreading the atheism speech. The present study follows the historical method and the descriptive analysis reach to the objective fact.